PERANCANGAN SISTEM INFORMASI PERHITUNGAN PELANGGARAN SISWA MENGGUNAKAN METODE SAW BERBASIS WEBSITE (STUDI KASUS : SMP NEGERI 2 TEMBELANG) - Ovi Fitri Satriyati; Anita Andriani; Ginanjar Setyo Permadi; Muhammad Fatkhur Rizal (Fakultas Teknologi Informasi, 2025)
The implementation of school regulations plays an important role in shaping students' character and discipline. However, at SMP Negeri 2 Tembelang, the recording of student violations is still done manually by the guidance and counseling (BK) teacher, which makes the data prone to being lost, difficult to trace, and slow in supporting decision-making. This study aims to design and develop a web-based student violation scoring information system using the Simple Additive Weighting (SAW) method, which can assist the school in evaluating and classifying the level of violations objectively, quickly, and accurately. The SAW method is used to calculate violation scores based on several predetermined criteria, such as attitude and behavior, neatness, diligence, and the type of violation committed by the student. The system development process consists of the phases of requirements analysis, system design with UML, website implementation with PHP and MySQL and system testing with the black box method. The result of this research is a web-based information system application that can be used by administrators, BK teachers, classroom teachers, and guardians to record violations, calculate points, and display the results of classifying students' violation levels (mild, moderate, serious). The system is also equipped with an internal communication feature between school parties. System tests show that all functions work as expected. This system is intended to increase the efficiency of recording student violations and support the ongoing process of character development.